Do tédio ao caos, do caos à lama: os primeiros capítulos da cena musical Mangue, Recife - 1980-1991 - Ribeiro, Getulio (2007)
This work investigates and make historical reflection about the creation and trajectory, throughout the 80 s, of a group of friends who together would come to create, in Recife/PE, in the earlies 1990, the mangue scene or Manguebeat Movement. Throughout this passage, we take as primordial objects: the creation, at 1984, and the trajectory of Mundo Livre S/A band; the radio program Décadas, presented between 1985 and 1987; and the musical experience of Bom Tom Rádio (possessing in its formation the deceased singer and composer Chico Science), between years 1987 and 1990. This work investigates the practice of the involved subjects in these processes, in concurrence with the historical transformations in the social and cultural life of Recife throughout the 80 s. Detached, on the part of our objects, the development of practices that inaugurate new ways of act and think about city s cotidian and its own place about the world, using music as critic expeditious and central agglutinant axle. In elapsing of the reflection, is also mobilized series of problems relative to the youthful pop culture of 1980 s in Brazil and all around the world, in the effort to get a better comprehension of our object in association with feeling structures wich are inscribled on the historical experience of a hole generation. The present discussion is realized with the analysis of audio registers of shows, assays, amateur and studio registers of the bands, scripts, and audio registers of the radio programs. We also use particular interviews done with integrants of the bands and the producers/presenters of Décadas program, such as: Fred Zeroquatro (Mundo Livre S/A singer and Décadas producer), Renato Lins (journalist and Décadas producer) and José Carlos Arcoverde (Decades producer and presenter and Bom Tom Rádio member).